Patterns of Utilization of Maternal and Child Health Care among Tribals of H D Kote Taluk Mysore - Kavita Yadav; Narayana Murthy MR; Manohar Prasad; Praveen Kulkarni (Indian Journal of Medical Specialities)
Background: Maternal and child health (MCH) care services utilization is an important issue in the tribal area. It is very important to understand the pattern of utilization so as enable the policymakers to take initiatives to make the service provision more acceptable to the tribal population of India. Methodology: A community-based study was conducted in the tribal area of H D Kote taluk Mysore. Of 16 Primary Health Centers, five centers which cover nearly 50% of the population were chosen for the study. All the mothers who resided in those areas and delivered during January 2013 to December 2013, were chosen for study, which came to 215. Those who had migrated to areas outside our study area and those who were not found in home during data collection home visit were left out. Hence, the final sample size came to be 165. Results: Majority of mothers (74.5%) had antenatal registration done in the first trimester. Nearly 36.4% of mothers had <3 antenatal check-up visits, 26.7% had 3–5 visits, and 32.7% of mothers had >5 visits. About 95.2% of mothers had received two Tetanus toxoid injections, 3% had one injection, and 1.8% had no injections. About 42.4% of mothers had consumed >100 iron and folic acid (IFA) tablets, 27.3% had 75–100 tablets, 13.3% had 50–75 tablets, and 14.5% had <50 tablets, whereas 2.4% did not consume the IFA tablets. Conclusion: MCH care services utilization in the chosen tribal area was found to be satisfactory. It is a good sign as this reflects on the success of the reach of the government programs aimed at improving the mother and child health conditions in the tribal population.